Review Paper on Cryptography Algorithms Used in Wireless Sensor Networks - Kaur, H; Kaur, K (International Journal of Computer Sciences and Engineering, 2018)
Wireless sensor network are autonomous nodes which monitor and communicate the sensor data to central unit through wireless network. There devices are installed in the remote areas and used for communicate sensitive information in different application such as smart grids, MANET. The attackers attack on these nodes to extract information or modify. In this paper, various attacks and its countermeasure technique such as cryptography algorithms are studied and comparative analysis is done for the wireless sensor network. From, the analysis found that symmetric and asymmetric ciphers are hybrid which provide authentication and confidentiality but increased the resources requirement. But, the wireless sensor nodes are battery operated and low memory available. Therefore, we recommend in the future work preferred lightweight cipher and different modes of authentication such as CCM, counter mode to enhance the performance on wireless sensor network.